(untitled) (Research, Society and Development, 2021)
Aim: The aim of this systematic review is to evaluate the influence of the different concentrations of hydrofluoric acid (HF) on the etching of glass ceramics. Materials and Methods: This review searched in vitro studies on the Cochrane Library, Lilacs, PubMed, SciElo, Scopus and Web of Science, using the keywords “Veneers”, “Crowns”, “Ceramics”, “Ceramic”, “Surface Treatments”, “Surface”, “Acid Concentration”, “Hydrofluoric Acid Concentration”, “Adhesion”, “Hydrofluoric Acid”. Studies that investigated the effects of the HF concentration in groups with different concentrations were included. The level of evidence of the selected articles followed the principles of the Oxford Center for Evidence-Based Medicine. This review followed the recommendation of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyzes). In the studies, different types of concentration were used on the ceramics, and, in general, the 5% HF concentration had the best performance. Results: The searching strategy found 151 titles, from which 8 were selected and included in the review. The standards of evaluation included the influence of acid concentration in flexural resistance, surface roughness, contact angle and micro shear resistance. Conclusion: The studies found more negative results in lower concentrations (1% and 3%). In spite of some advantages, the 10% HF also did not present the best results, when compared to 5% HF. Moreover, the concentration should not be seen as the only and most important factor of the quality of ceramics adhesion.